Transient Gene Expression as a Tool to Monitor and Manipulate the Levels of Acidic Phospholipids in Plant Cells - Noack, Lise C; Pejchar, Přemysl; Sekereš, Juraj; Jaillais, Yvon; Potocký, Martin (Methods in molecular biology, 2019)
Anionic phospholipids represent only minor fraction of cell membranes lipids but they are critically important for many membrane-related processes, including membrane identity, charge, shape, the generation of second messengers, and the recruitment of peripheral proteins. The main anionic phospholipids of the plasma membrane are phosphoinositides phosphatidylinositol 4-phosphate (PI4P), phosphatidylinositol 4,5-bisphosphate (PI4,5P2), phosphatidylserine (PS), and phosphatidic acid (PA). Recent insights in the understanding of the nature of protein-phospholipid interactions enabled the design of genetically encoded fluorescent molecular probes that can interact with various phospholipids in a specific manner allowing their imaging in live cells. Here, we describe the use of transiently transformed plant cells to study phospholipid-dependent membrane recruitment.
Keywords: Luminescent Proteins; Plant Cells; Fluorescent Dyes; Microscopy, Fluorescence; Nicotiana; fosfolipidy; fluorescenční barviva; transformace genetická; fluorescenční mikroskopie; fosfatidylinositoly; rostlinné buňky; luminescentní proteiny; Phospholipids; Pollen; pyl; Transformation, Genetic; exprese genu; Phosphatidylinositols; Microscopy, Confocal; konfokální mikroskopie; tabák; Gene Expression